Constituição da memória por meio do Acervo Digital TV UNESP Assis - Toller, Mariana Escher [UNESP]; Galhardo, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The university television (TV) was created in 1968 in Brazil and nowadays its programming is transmitted by cable TV. In fact, this only occurred in January 1995 after the enactment of Law No. 8977. This law aroused the interest of higher education institutions in expanding knowledge, leading to the creation of several university stations. Since then the university TV proved to be important for the history preservation of both university and society. Particularly the UNESP TV was created in order to inform the community residents. However it goes further: the UNESP also contributes for the formation of political and social identity of both students and community residents. Considering that the schedule produced by the UNESP TV is an ‘institutional memory’, our aim is to evaluate the role of the university TV in preserving the history of the UNESP campus Assis.

A televisão universitária surgiu no Brasil em 1968. Atualmente o canal universitário é transmitido na TV a cabo, após a promulgação da Lei n° 8977, em janeiro de 1995. Esta Lei despertou o interesse das Instituições de Ensino Superior em expandir o conhecimento, acelerando a criação de várias emissoras universitárias. Desde então a TV universitária provou ser importante para a preservação da história da universidade e da sociedade na qual está inserida. De particular interesse, a TV UNESP ASSIS foi criada principalmente para informar a comunidade sobre o meio acadêmico. Entretanto, ela vai além e contribui para a formação da identidade política e social tanto de estudantes quanto da comunidade em geral. Considerando que a programação da TV UNESP faz parte da memória institucional, este trabalho tem como objetivo avaliar o papel da TV universitária na preservação da história do campus UNESP Assis.
Keywords: University TV; Digital repositories; Memory; TV universitária; Repositórios digitais; Memória